USE OF MODERN PEDAGOGICAL TECHNOLOGIES AND INTERACTIVE METHODS IN FINE ART. - Alisher Latipovich Shirinov (Scholar Express Journal, 2021)
In the process of training, the creation of problem situations on the topic using modern methods and information technology, the organization of lectures, seminars, travels, debates, conversations, conferences, problemsolving lessons, ensuring their successful solution is of particular importance. The fact that pedagogical technology is a project of a certain pedagogical system that is implemented in practice is of great interest to many.
Keywords: Modern methods; information technology; lectures; seminars